Respiratory system pathologies in patients who underwent total laryngectomy due to larynx cancer - Hakan Celikhisar (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Aim: The aim of the present study was to examine the long-term respiratory system pathologies that may develop in larynx cancer patients who have undergone total laryngectomy operation.  Method: A total of 54 larynx cancer patients who have undergone total laryngectomy operation admitted to our clinic during July 2016 - November 2019 due to accompanying respiratory system pathology were retrospectively evaluated with regard to clinical radiologic and histopathologic findings. The findings were examined comparatively with relevant literature data.  Results: All cases were male with an age average of 65+8 years. The cases had a smoking history of 62+42 packs/year on average. All cases had been subject to total laryngectomy operation due to epidermoid type larynx carcinoma and they had tracheostomy. Non-small cell lung carcinoma was determined in 14 cases (26 %), chronic obstructive pulmonary disease (COPD) in 12 cases (22 %), pneumonia in 8 cases (15 %), inactive lung tuberculosis in 4 cases (7.5 %), malignant pleurisy in 2 cases (3.75 %) and metastatic lung cancer in 2 cases (3.75 %).  Conclusion: The pathologies observed in the cases were predominantly evaluated secondary to tracheostomy and epidemiologic factors such as smoking. It was concluded that operated larynx cancer cases should be followed up at frequent intervals with regard to other respiratory system pathologies that may develop.